Liquid crystal display screen protective film and preparation method and application thereof

By using a liquid crystal display protective film composed of a PET bonding layer, a glue layer and an anti-static PET substrate layer, and using adhesives made of epoxy acrylate, fluoro-containing acrylate and other materials, the problems of light reflection, edge curling and bubbles in high-precision and high-resolution liquid crystal displays are solved, and better fit stability and peeling performance are achieved.

CN118725800BActive Publication Date: 2025-03-25GUANGDONG HONGQING ELECTRONICS MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410755080.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-03-25
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The existing LCD display protective film is prone to reflection, corner areas and bubbles in high-precision and high-resolution LCD screens, which affects the use effect.

Method used

The liquid crystal display protective film consisting of a PET bonding layer, a glue layer and an anti-static PET substrate layer is made of adhesive made of epoxy acrylate, fluoro-containing acrylate, polydimethylsiloxane/acrylic copolymer and other materials, and has good light transmittance, heat resistance and bonding stability.

Benefits of technology

It is achieved that the reflection is not easy to appear in high-precision and high-resolution LCD screens, and it is not easy to appear to be curled and bubbles in long-term use. It is easy to tear off when replacing, and it is not easy to have residual glue, which improves the applicability and service life of the protective film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118725800B_ABST
    Figure CN118725800B_ABST
Patent Text Reader

Abstract

The present application relates to the field of protective films, and discloses a liquid crystal display screen protective film and its preparation method and process. A liquid crystal display screen protective film, from the inside to the outside, consists of a PET laminating layer, a glue layer, and an antistatic PET substrate layer, and the glue layer is cured by curing an adhesive made from the following raw materials in parts by weight: 50-80 parts of epoxy acrylate, 10-20 parts of fluorinated acrylate, 5-15 parts of polydimethylsiloxane / acrylic copolymer, 10-20 parts of diluent, 3-8 parts of photoinitiator, 3-6 parts of stabilizer, and 0.5-2 parts of antioxidant; preparation method: the adhesive is applied to the antistatic PET substrate layer and cured by ultraviolet light to form a glue layer, and the PET laminating layer is laminated. The liquid crystal display screen protective film of the present application has good light transmittance, heat resistance and laminating stability, is suitable for high-precision and high-resolution liquid crystal displays, has good texture, is not easy to reflect light, is not prone to warping and bubbles in long-term use, and has no residual glue after tearing off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of protective films, and more specifically, to a liquid crystal display protective film and a preparation method and application thereof. Background Art

[0002] With the continuous development of electronic products, LCD screens are becoming more and more integrated and ultra-thin. The accuracy and resolution of LCD screens are getting higher and higher, and the requirements for texture are getting higher and higher. In order to prevent the surface of LCD screens from being easily bumped or scratched during production, transportation and use, a protective film is generally attached to the surface of the LCD screen. Therefore, the requirements for the protective film used on the LCD screen are getting higher and higher.

[0003] The protective film used for LCD screens needs to have good scratch resistance and flexibility and bend resistance. It is generally made of PVC or PET as the substrate, and acrylic glue is coated on the surface of the substrate. The protective film made in this way can meet the above performance requirements; however, when this protective film is used in high-precision and high-resolution LCD screens, due to the high picture texture and color saturation, the LCD screen is prone to reflection, affecting the viewing comfort; and high-precision and high-resolution LCD screens are more likely to heat up during long-term operation, and the corners of the protective film are prone to warping and bubbles, reducing the applicability of the protective film. Summary of the invention

[0004] In order to solve the problems that the existing protective film is prone to reflection, warping and bubbles in the corner areas when used in high-precision and high-resolution liquid crystal displays, the present application provides a liquid crystal display protective film and a preparation method and application thereof.

[0005] In a first aspect, the present application provides a liquid crystal display screen protective film, which adopts the following technical solution:

[0006] A liquid crystal display screen protective film, which is composed of a PET laminating layer, a glue layer and an antistatic PET substrate layer from the inside to the outside, wherein the glue layer is prepared by curing an adhesive, and the adhesive is prepared from the following raw materials in parts by weight:

[0007]

[0008] By adopting the above technical scheme, the liquid crystal display screen protective film of the present application is composed of four material layers, the outermost layer is an antistatic PET substrate layer, which plays the role of anti-static and anti-dust, and at the same time has a good protection and support function to prevent the liquid crystal display screen from being scratched by collision; the glue layer plays a bonding role, so that the protective film is stably attached to the liquid crystal display screen; the PET bonding layer protects the glue layer and needs to be torn off when in use.

[0009] In order to improve the applicability of LCD screen protective films in high-precision and high-resolution LCD screens, the adhesive of the present application is cured to prepare a glue layer, which has good light transmittance, heat resistance and bonding stability, is not easy to reflect light, and has a good viewing texture; it is not easy to have problems such as warping and bubbles after long-term use, and it is easy to tear off when it needs to be replaced, and it is not easy to have residual glue.

[0010] The adhesive of the present application uses epoxy acrylate as a resin matrix, and is compounded with fluorinated acrylate and polydimethylsiloxane / acrylic copolymer. The fluorinated acrylate can have a good compounding performance with epoxy acrylate, improve the bonding stability of the adhesive, and make the prepared protective film less likely to warp and bubble. The polydimethylsiloxane / acrylic copolymer can produce a good synergistic effect with the fluorinated acrylate and the acrylate resin, so that the adhesive has a good cohesive force, and thus the protective film has a good bonding stability and a good peeling performance, and is less likely to have residual adhesive. The diluent plays a role in adjusting the viscosity and processing fluidity of the resin matrix, and can further undergo a polymerization reaction with the resin matrix to improve the bonding stability of the adhesive. The photoinitiator plays a role in initiating the polymerization reaction. The stabilizer can have a good synergistic effect with the fluorinated acrylate and the polydimethylsiloxane / acrylic copolymer, further improving the bonding performance and glass performance of the adhesive, so that the protective film has a good bonding stability and a good peeling performance.

[0011] Preferably, the fluorinated acrylate is prepared from the following raw materials in parts by weight:

[0012] Perfluorohexylethyl acrylate 6-12 parts

[0013] Trimethylolpropane trimethacrylate 30-40 parts

[0014] 4-8 parts of dimethacrylate urethane

[0015] Allyl glycidyl ether 3-6 parts

[0016] 0.2-0.5 parts of dibenzoyl peroxide.

[0017] By adopting the above technical scheme, under the condition of dibenzoyl peroxide as a catalyst, perfluorohexyl ethyl acrylate is used as a fluorine-containing monomer, dimethacrylate carbamate is used as an amino-containing monomer, and trimethylolpropane trimethacrylate is polymerized to introduce fluorine-containing segments and amino segments into the acrylate segments. The obtained fluorine-containing acrylate is applied to the adhesive, which can improve the bonding stability and heat resistance of the adhesive, so that the protective film is not prone to warping and bubbling problems when used under long-term high-temperature conditions, and has good bonding stability. Allyl glycidyl ether has active vinyl and soft ether segments, which can further improve the polymerization performance of perfluorohexyl ethyl acrylate, dimethacrylate carbamate and trimethylolpropane trimethacrylate, and further improve the bonding stability of the adhesive.

[0018] Preferably, the fluorinated acrylate is prepared by the following steps:

[0019] Perfluorohexyl ethyl acrylate, trimethylolpropane trimethacrylate, dimethacrylate carbamate, allyl glycidyl ether and dibenzoyl peroxide are added into a reaction device, vacuumed and heated for reaction to prepare fluorine-containing acrylate.

[0020] By adopting the technical scheme, under vacuum and heating conditions, using dibenzoyl peroxide as a catalyst, the monomers are polymerized to prepare a fluorine-containing acrylate with stable performance.

[0021] Preferably, the vacuum degree of the vacuum extraction is -0.08-0.1 MPa, the reaction temperature is 60-80°C, and the reaction time is 1-2h.

[0022] By adopting the above technical solution, the polymerization reaction efficiency can be improved by controlling the optimal reaction vacuum degree, reaction temperature and reaction time.

[0023] Preferably, the diluent is composed of methyl methacrylate, lauryl acrylate and glycidyl methacrylate in a weight ratio of 1:(2-3):(0.2-0.5).

[0024] By adopting the above technical solution, methyl methacrylate is used as a hard monomer, lauryl acrylate is used as a soft monomer, and glycidyl methacrylate is used as a functional monomer, which can undergo polymerization reaction with epoxy acrylate to improve the bonding stability of the prepared adhesive.

[0025] Preferably, the stabilizer is composed of a vinyl silane coupling agent and dibutyl itaconate in a weight ratio of 1:(2-4).

[0026] By adopting the above technical scheme, dibutyl itaconate can enhance the cohesive force of the adhesive, so that the adhesive has good bonding stability and good peeling performance, and reduces the residual adhesive. The use of vinyl silane coupling agent and dibutyl itaconate in an optimal dosage ratio as a stabilizer can produce a good synergistic effect with fluorinated acrylates and polydimethylsiloxane / acrylic acid copolymers, thereby improving the bonding stability and peeling performance of the prepared adhesive.

[0027] Preferably, the photoinitiator is any one of 1-hydroxycyclohexyl phenyl ketone and / or 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0028] By adopting the above technical solution and using the above raw materials as photoinitiators, the adhesive can be cured under better photocuring conditions, thereby improving the curing efficiency and reducing the curing energy consumption.

[0029] Preferably, the antioxidant is a hindered phenol antioxidant and / or a phosphate antioxidant.

[0030] By adopting the above technical solution, the above antioxidant can improve the antioxidant performance of the adhesive, and further improve the temperature resistance and service life of the protective film.

[0031] In a second aspect, the present application provides a method for preparing a liquid crystal display protective film, which adopts the following technical solution: A method for preparing a liquid crystal display protective film, comprising the following preparation steps:

[0032] S1, applying the adhesive to the surface of the antistatic PET substrate layer, and performing UV curing to form a glue layer;

[0033] S2, laminating the PET laminating layer to one side of the glue layer to obtain a preliminary product of the liquid crystal display screen protective film;

[0034] S3, placing the initial product of the liquid crystal display protective film at a temperature of 40-50° C. for heat preservation, cooling, and obtaining the liquid crystal display protective film.

[0035] By adopting the above technical solution, a liquid crystal display screen protective film with good lamination stability is prepared.

[0036] In a third aspect, the present application provides an application of a liquid crystal display screen protective film, which is used in protecting high-precision and high-resolution liquid crystal display screens.

[0037] In summary, this application has the following beneficial effects:

[0038] 1. The liquid crystal display protective film of the present application is composed of an antistatic PET substrate layer, a glue layer and a PET bonding layer from the outside to the inside. The glue layer is made by curing an adhesive made of epoxy acrylate, fluorinated acrylate, polydimethylsiloxane / acrylic copolymer, diluent, photoinitiator, stabilizer and antioxidant. It has good light transmittance, heat resistance and bonding stability, is not easy to reflect light, and has a good viewing texture. It is not easy to have problems such as warping and bubbles in long-term use, and it is easy to tear off when it needs to be replaced, and it is not easy to have residual glue.

[0039] 2. By using fluorinated acrylates made from perfluorohexyl ethyl acrylate, trimethylolpropane trimethacrylate, dimethacrylate urethane, allyl glycidyl ether and dibenzoyl peroxide, the bonding stability and heat resistance of the adhesive can be improved, making it less likely for the protective film to have problems such as edge warping and bubbles when used under long-term high-temperature conditions, and having better bonding stability.

[0040] 3. By using vinyl silane coupling agent and dibutyl itaconate as stabilizers, a good synergistic effect can be produced with fluorinated acrylate and polydimethylsiloxane / acrylic acid copolymer, thereby improving the bonding stability and peeling performance of the prepared adhesive.

[0041] 4. The LCD protective film of the present application is suitable for high-precision and high-resolution LCDs. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a longitudinal cross-sectional schematic diagram of a liquid crystal display screen protective film of the present application.

[0043] Explanation of the accompanying drawings: 1. Antistatic PET substrate layer; 2. Glue layer; 3. PET laminating layer. DETAILED DESCRIPTION

[0044] The following is combined with Figure 1 The present application is further described in detail with reference to the accompanying drawings and embodiments.

[0045] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used:

[0046] 1. Epoxy acrylate: Allnex EB6040 or Allnex EB3740;

[0047] 2. Perfluorohexylethyl acrylate: KMIKE, CAS No. 17527-29-6, content 98%;

[0048] 3. Polydimethylsiloxane / acrylic acid copolymer: g / m, hydroxyl value mgKOH / g, PEG / PPG-25 / 30 copolymer;

[0049] 4. Trimethylolpropane trimethacrylate: TMPTA, CAS No. 3290-92-4, content 99%;

[0050] 5. Dimethacrylate urethane: CAS No. 72869-86-4, content 99%;

[0051] 6. Dibutyl itaconate: CAS No. 2155-60-4, content 99%;

[0052] 7. Trifluoroethyl methacrylate: CAS No. 352-87-4, content 99%;

[0053] 8. Antistatic PET substrate layer: AR-grade high-transmittance antistatic PET protective film, with a transmittance greater than 98% and a thickness of 50U, 75U or 100U;

[0054] 9. PET laminating layer: AR grade high light transmittance PET release film, release force 3-8g, thickness of 25U, 36U or 50U.

[0055] Preparation Example of Fluorinated Acrylate

[0056] Preparation Example 1

[0057] Preparation Example 1 discloses a fluorine-containing acrylate, which is prepared by the following steps: 1.2 kg of perfluorohexyl ethyl acrylate, 3 kg of trimethylolpropane trimethacrylate, 0.4 kg of dimethacrylate carbamate, 0.3 kg of allyl glycidyl ether and 0.02 kg of dibenzoyl peroxide are added to a reaction kettle, evacuated to a vacuum degree of -0.08 MPa, and heated to 60°C, reacted for 1 hour, to obtain a fluorine-containing acrylate.

[0058] Preparation Example 2-3

[0059] The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.

[0060] Table 1 Raw material dosage and preparation conditions of Preparation Examples 1-3

[0061]

[0062] Preparation Comparative Example 1

[0063] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of dimethacrylate carbamate is replaced by perfluorohexylethyl acrylate, and the rest is the same as Preparation Example 1.

[0064] Preparation Comparative Example 2

[0065] The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of trimethylolpropane trimethacrylate is replaced by 2-hydroxyethyl acrylate, and the rest is the same as Preparation Example 1.

[0066] Preparation Comparative Example 3

[0067] The difference between Preparation Comparative Example 3 and Preparation Example 1 is that allyl glycidyl ether is quantitatively replaced with trimethylolpropane trimethacrylate, and the rest is the same as Preparation Example 1.

[0068] Example

[0069] Example 1

[0070] Example 1 discloses a liquid crystal display screen protective film, referring to Figure 1 , including an antistatic PET substrate 1, a glue layer 2 and a PET laminating layer 3 which are sequentially laminated from the outside to the inside. The thickness of the antistatic PET substrate layer 1 is 100U, the thickness of the PET laminating layer 3 is 50U, and the glue layer 2 is made of a cured adhesive.

[0071] The liquid crystal display screen protective film is prepared by the following steps:

[0072] S1, apply adhesive at 10g / m 2 The coating amount was applied to the surface of the antistatic PET substrate layer, and a UV curing machine was used at a curing energy of 1100mj / cm 2 Curing for 2 minutes under the conditions to form a glue layer;

[0073] S2, laminating the PET laminating layer to one side of the glue layer to obtain a preliminary product of the liquid crystal display screen protective film;

[0074] S3. Place the initial product of the liquid crystal display protective film at a temperature of 40° C. for 30 minutes, cool it at room temperature, cut it, and roll it up to obtain the liquid crystal display protective film.

[0075] Among them, the adhesive is prepared by the following steps: 5kg of Allnex EB6040 as epoxy acrylate, 1kg of perfluorohexylethyl acrylate as fluorine-containing acrylate, 0.5kg of polydimethylsiloxane / acrylic copolymer, 1kg of diluent (composed of methyl methacrylate, lauryl acrylate and glycidyl methacrylate in a weight ratio of 1:2:0.2) and 0.3kg of vinyltrimethoxysilane as a stabilizer are added into a mixer, the temperature is raised to 45°C, mixed for 20 minutes, and after mixing evenly, 0.3kg of 1-hydroxycyclohexyl phenyl ketone as a photoinitiator and 0.05kg of antioxidant (composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1) are added, mixed for 10 minutes, mixed evenly, and the adhesive is prepared.

[0076] Example 2-3

[0077] The difference between Example 2-3 and Example 1 is that the parameters of the preparation method of the liquid crystal display screen protective film are different, and the amount of raw materials and preparation conditions of the adhesive are also different, see Table 2 below for details.

[0078] Table 2 Process parameters and preparation table of adhesives of Examples 1-3

[0079]

[0080]

[0081]

[0082] Embodiment 4-9

[0083] The difference between Examples 4-9 and Example 1 is that the sources of the adhesive are different, see Table 3 below for details.

[0084] Table 3 Sources of adhesives in Examples 4-9

[0085] Example Source of Adhesive Example 4 Preparation Example 1 Example 5 Preparation Example 2 Example 6 Preparation Example 3 Example 7 Preparation Comparative Example 1 Example 8 Preparation Comparative Example 2 Example 9 Preparation Comparative Example 3

[0086] Example 10

[0087] The difference between Example 10 and Example 4 is that the stabilizer is different. The stabilizer in Example 10 is composed of vinyltrimethoxysilane and dibutyl itaconate in a weight ratio of 1:2, and the rest is the same as Example 4.

[0088] Embodiment 11

[0089] The difference between Example 11 and Example 10 is that the stabilizer consists of vinyltrimethoxysilane and dibutyl itaconate in a weight ratio of 1:4, and the rest is the same as Example 10.

[0090] Comparative Example

[0091] Comparative Example 1

[0092] The difference between Comparative Example 1 and Example 1 is that an equal amount of fluorinated acrylate is replaced by epoxy acrylate, and the rest is the same as Example 1.

[0093] Comparative Example 2

[0094] The difference between Comparative Example 2 and Example 1 is that the polydimethylsiloxane / acrylic copolymer is replaced by epoxy acrylate in equal amounts, and the rest is the same as Example 1.

[0095] Comparative Example 3

[0096] The difference between Comparative Example 3 and Example 1 is that an equal amount of epoxy acrylate is replaced by acrylic resin, and the acrylic resin comes from Allnex EB854. The rest is the same as Example 1.

[0097] Comparative Example 4

[0098] The difference between Comparative Example 4 and Example 1 is that the stabilizer is replaced by an equal amount of fluorinated acrylate, the fluorinated acrylate is perfluorohexylethyl acrylate, and the rest is the same as Example 1.

[0099] Performance testing

[0100] The performance tests of the liquid crystal display screen protective films prepared in Examples 1-11 and Comparative Examples 1-4 are as follows:

[0101] 1. Light transmittance test:

[0102] Referring to the test method in GB T 2410-2008, tear off the PET laminating layer of the LCD screen protective film, and then perform a light transmittance (unit: %) test, test and record the test results;

[0103] 2. Peel force test

[0104] Referring to the test method in GB / T 2792-2014, the glass substrate is used as the bonding test plate, and the peel strength (unit: N / 25mm) test is performed at a peeling angle of 90°, which is recorded as the first peel strength. The test results are tested and recorded;

[0105] 3. Fit stability test

[0106] The LCD screen protective film is attached to the surface of the glass substrate, placed in a constant temperature and humidity chamber at a temperature of 80°C and a humidity of 60%, tested for 48 hours, and observed for bubbles and edge warping; after being wiped dry and restored to room temperature, the peel strength (unit: N / 25mm) is tested at a peeling angle of 90° according to the test method in GB / T2792-2014, recorded as the second peeling strength, and the residual glue on the surface of the glass substrate is observed, and the test results are tested and recorded;

[0107] The following are the performance test data of the liquid crystal display screen protective films prepared in Examples 1-11 and Comparative Examples 1-4, see Table 4 below for details.

[0108] Table 4 Performance test data of Examples 1-11 and Comparative Examples 1-4

[0109]

[0110]

[0111] Combining Examples 1-3 and Comparative Examples 1-3 and Table 4, it can be concluded that the epoxy acrylate, fluorinated acrylate and polydimethylsiloxane / acrylic copolymer of the present application are compounded, and the three produce a good synergistic effect, which improves the bonding stability of the protective film, is not easy to warp and have bubbles, and also has good peelability and is not easy to produce residual glue; in Comparative Example 1, no fluorinated acrylate is added, the peel strength of the protective film obtained is significantly reduced, the bonding is unstable, and obvious warping and bubbles appear. It may be that no fluorinated acrylate is added, which significantly reduces the bonding performance of the protective film; in Comparative Example 2, no polydimethylsiloxane / acrylic copolymer is added, the peel strength of the protective film obtained is significantly improved, and after high temperature testing, a significant increase in peel strength occurs, and obvious residual glue appears during peeling; in Comparative Example 3, epoxy acrylate is replaced with acrylate, and the performance of the protective film obtained is reduced.

[0112] Combining Example 1 and Examples 4-9 and Table 4, it can be concluded that the use of the fluorinated acrylate prepared by the present application can further improve the bonding stability of the prepared protective film, and has good peeling performance, further reducing the problems of warping and bubbles. In Example 1 and Examples 7-9, the fluorinated acrylate of the present application was not used, and the peel strength of the prepared protective film was reduced. The peel strength decreased after the high temperature test, and slight warping and bubbles occurred.

[0113] Combining Example 4 with Examples 10-11, Comparative Example 4 and Table 4, it can be concluded that the use of the preferred usage ratio of vinyl silane coupling agent and dibutyl itaconate as a stabilizer can further enhance the synergistic effect of epoxy acrylate, fluorinated acrylate and polydimethylsiloxane / acrylic copolymer, so that the prepared protective film has good adhesion stability and good peeling performance, and the bonding is stable and no residual glue will appear when peeling; in Comparative Example 4, the stabilizer is replaced with fluorinated acrylate, and the peel strength of the prepared protective film is improved, and after high temperature testing, the peel strength increases, and residual glue will appear during peeling.

[0114] From the above, it can be seen that the LCD screen protective film of the present application has good light transmittance, with the highest transmittance reaching 97.8%, is not easy to reflect light, and has good picture fidelity and viewing texture performance; it has good bonding stability, and is not prone to warping and bubbles after long-term high-temperature use; it also has good peeling performance, and there will be no residual glue after peeling, and it is particularly suitable for high-precision and high-resolution LCD screens.

[0115] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A liquid crystal display screen protective film, characterized in that: From the inside to the outside, it is composed of a PET laminating layer, a glue layer and an antistatic PET substrate layer. The glue layer is made by curing an adhesive, and the adhesive is made of the following raw materials in parts by weight: Epoxy acrylate 50-80 parts Fluorinated acrylate 10-20 parts Polydimethylsiloxane / acrylic acid copolymer 5-15 parts 10-20 parts of diluent Photoinitiator 3-8 parts 3-6 parts of stabilizer 0.5-2 parts of antioxidant; The fluorinated acrylate is prepared from the following raw materials in parts by weight: Perfluorohexylethyl acrylate 6-12 parts Trimethylolpropane trimethacrylate 30-40 parts 4-8 parts of dimethacrylate urethane Allyl glycidyl ether 3-6 parts Benzoyl peroxide 0.2-0.5 parts; The fluorinated acrylate is prepared by the following steps: Perfluorohexyl ethyl acrylate, trimethylolpropane trimethacrylate, dimethacrylate carbamate, allyl glycidyl ether and dibenzoyl peroxide are added into a reaction device, vacuumed and heated for reaction to prepare fluorine-containing acrylate.

2. A liquid crystal display screen protective film according to claim 1, characterized in that: The vacuum degree of the vacuum extraction is -0.08-0.1MPa, the reaction temperature is 60-80°C, and the reaction time is 1-2h.

3. The liquid crystal display screen protective film according to claim 1, characterized in that: The diluent is composed of methyl methacrylate, lauryl acrylate and glycidyl methacrylate in a weight ratio of 1:(2-3):(0.2-0.5).

4. The liquid crystal display screen protective film according to claim 1, characterized in that: The stabilizer consists of a vinyl silane coupling agent and dibutyl itaconate in a weight ratio of 1:(2-4).

5. The liquid crystal display screen protective film according to claim 1, characterized in that: The photoinitiator is any one of 1-hydroxycyclohexyl phenyl ketone and / or 2-hydroxy-2-methyl-1-phenyl-1-propanone.

6. The liquid crystal display screen protective film according to claim 1, characterized in that: The antioxidant is a hindered phenol antioxidant and / or a phosphate antioxidant.

7. A method for preparing a liquid crystal display protective film according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: S1, applying the adhesive to the surface of the antistatic PET substrate layer, and performing UV curing to form a glue layer; S2, laminating the PET laminating layer to one side of the glue layer to obtain a preliminary product of the liquid crystal display screen protective film; S3, placing the initial product of the liquid crystal display protective film at a temperature of 40-50° C. for heat preservation, cooling, and obtaining the liquid crystal display protective film.

8. An application of the liquid crystal display protective film according to any one of claims 1 to 6, characterized in that: The liquid crystal display screen protective film is applied to liquid crystal display screens with high precision and high resolution.

Citation Information

Patent Citations

  • Adhesive applied to AF display screen protective film, preparation method of adhesive and protective film

    CN112961613A

  • Low-refractive-index photocuring adhesive and preparation method thereof

    CN116496749A